A Push–Pull PdII Complex with a Ternary Pd–P–C+ Accepting End and a Key N‐Heterocyclic Carbene–Imidazoliophosphine Ligand. Issue 3 (21st January 2016) - Dubrulle, Laurent; Poidevin, Corentin; Maaliki, Carine; Canac, Yves; Lepetit, Christine; Duhayon, Carine; Chauvin, Remi
Abstract: Invited for the cover of this issue is the group of Remi Chauvin from the Laboratoire de Chimie de Coordination, Toulouse, France. The cover image shows the polarization of a neutral Pd II complex in three steps presented on three levels of the marine background. Abstract : The original idea was just to combine, within the same chemical entity, two types of structural units that were hitherto complementary at the conceptual level only... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 313 ff .